Systematic pathological component scores for skin-containing vascularized composite allografts. (10th October 2016) - Rosales, Ivy A.; Foreman, Ruth K.; DeFazio, Matthew; Sachs, David H.; Cetrulo, Curtis L.; Leonard, David A.; Colvin, Robert B.
ABSTRACT: Clinical management of skin-containing vascularized composite allografts (VCA) requires accurate assessment of the graft status, typically based on skin biopsies. The Banff 2007 Working Classification proposed 4 grades of acute rejection, but did not score individual features or include vascular rejection. Here we report a systematic scoring system developed from MHC-mismatched porcine skin-containing VCA. Biopsies from 20 VCA, 9 autologous skin flaps and 9 normal skin were analyzed to optimize the methodology and set thresholds. The components quantified were: perivascular cells/dermal vessel (pc), perivascular dermal infiltrate area (pa), luminal leukocytes/capillary or venule (c), epidermal infiltrate (ei), epidermal apoptosis or necrosis (e), endarteritis (v), and chronic allograft vasculopathy (cav). To evaluate prognostic value, we scored a separate group of 28 serial biopsies from 8 recipients (4 that were ultimately accepted and 4 that rejected. Parameters on the initial biopsies predicting later graft rejection included pc (p < 0.02), pa (p < 0.03), ei (p < 0.0005), e (p < 0.003) and c (p < 0.005). Reproducibility between 2 pathologists blinded to clinical data was acceptable, with weighted kappa scores for pc (0.673), pa (0.399), ei (0.464), e (0.663), v (0.766), and c (0.642). This component scoring system can be adapted clinically, since human and porcine skin are highly similar. Vascular lesions in VCA are also highlighted in this system and could impact graft outcome. The component score approach complements Banff 2007 grades and will enable the establishment of clinically significant thresholds.